Knowledge and Technology Transfer under Digital Conditions: Transfer Intermediaries in Eastern Germany and the Role of Digital Means, Trust and Face-to-Face Interactions - Anika Noack (Technische Hochschule Wildau und Brandenburgische Technische Universität Cottbus-Senftenberg, Innovation Hub 13 – fast track to transfer, 2022)
Even before the corona pandemic broke out in 2020, the role of digitalisation became more and more apparent within Knowledge and Technology Transfer (KTT) processes. Since the pandemic,intermediary organisations that bridge the distance between academia and the world of business to pave the way for successful university-industry linkages have not primarily been able to build on face-to-face-encounters to create those relations. Based on an ongoing research project, this paper examines how digitally mediated communications potentially enhance or limit knowledge and technology transfer that is primarily based on face-to-face interactions.On the one hand, the use of digitally mediated communications seem to foster the spatial expansion of networks, save travel times and costs and foster a special form of social inclusion. University-industry-relations, on the other hand,still rely on a positive evaluation of face-to-face contacts and geographical proximity for trust to develop between heterogeneous partners. Here, actors with bridging functions like transfer scouts are vital in enabling a regular communicative exchange to create commitment, social cohesion and cooperation in digital contexts. Although the relevance of digitalised transfer processes has been increasing over time, an important set of activities, involving face-to-face contacts and co-location, currently still plays a major role for transfer intermediaries in university-industry-relations. – – Der steigende Digitalisierungsgrad im Wissens und Technologietransfer (WTT) verändert die Praktiken von Transferintermediären dahingehend, dass diese zunehmend auf digital vermittelte Kommunikation anstelle persönlicher Begegnungen setzen müssen, um zwischen Wissenschaft und Wirtschaft zu vermitteln. Anika Noack (2022) zeigt im Beitrag, dass Akteure mit Brückenfunktionen – wie Transferscouts – zentral sind, um Kooperationsmöglichkeiten in digitalen Kontexten herzustellen.
urn:nbn:de:kobv:526-opus4-15711
Keywords: 330; Knowledge and technology transfer (KTT); transfer intermediaries; face-to-faceinteractions; mutual trust; focused ethnography